Answer:
[tex]x=-4[/tex]
[tex]y=3[/tex]
[tex]z=-5[/tex]
Step-by-step explanation:
Given:
[tex]x+y+z=-6[/tex]
[tex]x-6y-7z=-29[/tex]
[tex]-7y-5z=4[/tex]
Solve for [tex]x[/tex] in the 1st equation:
[tex]x+y+z=-6[/tex]
[tex]x+y=-z-6[/tex]
[tex]x=-y-z-6[/tex]
Substitute the value of [tex]x[/tex] into the 2nd equation and solve for [tex]z[/tex]:
[tex]x-6y-7z=-29[/tex]
[tex](-y-z-6)-6y-7=-29[/tex]
[tex]-7y-z-13=-29[/tex]
[tex]-7y-z=-16[/tex]
[tex]-z=-16+7y[/tex]
[tex]z=16-7y[/tex]
Substitute the value of [tex]z[/tex] into the 3rd equation and solve for [tex]y[/tex]:
[tex]-7y-5z=4[/tex]
[tex]-7y-5(16-7y)=4[/tex]
[tex]-7y-80+35y=4[/tex]
[tex]28y-80=4[/tex]
[tex]28y=84[/tex]
[tex]y=3[/tex]
Plug [tex]y=3[/tex] into the solved expression for [tex]z[/tex] and evaluate to solve for [tex]z[/tex]:
[tex]z=16-7(3)[/tex]
[tex]z=16-21[/tex]
[tex]z=-5[/tex]
Plug [tex]z=-5[/tex] into the solved expression for [tex]x[/tex] and evaluate to solve for [tex]x[/tex]:
[tex]x=-(3)-(-5)-6[/tex]
[tex]x=-3+5-6[/tex]
[tex]x=2-6[/tex]
[tex]x=-4[/tex]
Therefore:
[tex]x=-4[/tex]
[tex]y=3[/tex]
[tex]z=-5[/tex]